Sustained Effects of Acute Resistance Exercise on Executive Function in Healthy Middle-Aged Adults - Chou, Chien-Chih; Hsueh, Ming-Chun; Chiu, Yi-Hsiang; Wang, Wen-Yi; Huang, Mei-Yao; Huang, Chung-Ju (Frontiers in Human Neuroscience, 2021)
The present study examined the sustained effects of acute resistance exercise on inhibitory function in healthy middle-aged adults. Seventy healthy middle-aged adults (mean age = 46.98 ± 5.70 years) were randomly assigned to exercise or control groups, and the Stroop test was administered before, immediately after, and 40 min after exercise. The resistance exercise protocol involved two sets of seven exercises performed for a maximum of 10 repetitions, with 60 s between sets and exercises. Acute resistance exercise resulted in higher Stroop test performance under the incongruent (inhibition) and interference conditions immediately post-exercise and 40 min post-exercise. Furthermore, the difference in scores after 40 min was significant. The findings indicate that a moderately intensive acute resistance exercise could facilitate Stroop performance and has a more beneficial effect on sustaining of cognition that involves executive control at least 40 min.